Cysteine and glycine-rich protein 3 (Crp3) as a critical regulator of elastolysis, inflammation, and smooth muscle cell apoptosis in abdominal aortic aneurysm development - de Mattos, Ana Barbosa Marcondes; Ribeiro-Silva, Joao Carlos; Fonseca-Alaniz, Miriam Helena; Valadão, Iuri Cordeiro; da Silva, Erasmo Simão; Krieger, Jose Eduardo; Miyakawa, Ayumi Aurea (Frontiers in Physiology, 2023)
Abdominal aortic aneurysm (AAA) is a life-threatening vascular disease for which surgical or endovascular repair areis currently the the only currently available therapeutic strategiesy. The development of AAA involves the breakdown of elastic fibers (elastolysis), infiltration of inflammatory cells, and apoptosis of smooth muscle cells (SMCs). However, the specific regulators governing these responses remain unknown. We previously demonstrated that Cysteine and glycinerich protein 3 (Crp3) sensitizes SMCs to apoptosis induced by stretching. Building upon this finding, we aimed to investigate the influence of Crp3 on elastolysis and apoptosis during AAA development. Using the elastase-CaCl2 rat model, we observed an increase in Crp3 expression, aortic diameter, and a reduction in wall thickness in wild type rats. In contrast, Crp3 -/-rats exhibited a decreased incidence of AAA, with minimal or no changes in aortic diameter and thickness. Histopathological analysis revealed the absence of SMC apoptosis and degradation of elastic fibers in Crp3 -/-rats, accompanied by reduced inflammation and diminished proteolytic capacity in Crp3 -/-SMCs and bone marrowderived macrophages. Collectively, our findings provide evidence that Crp3 plays a crucial role in AAA development by modulating elastolysis, inflammation, and SMC apoptosis. These results 2 This is a provisional file, not the final typeset article underscore the potential significance of Crp3 in the context of AAA progression and offer new insights into therapeutic targets for this disease.